2016
DOI: 10.1002/anie.201607388
|View full text |Cite
|
Sign up to set email alerts
|

Highly ortho‐Selective Chlorination of Anilines Using a Secondary Ammonium Salt Organocatalyst

Abstract: An organocatalytic, highly facile, efficient, and regioselective ortho-chlorination of anilines is described. A secondary ammonium chloride salt has been employed as the catalyst and the reaction can be conducted at room temperature without protection from air and moisture. In addition, the reaction is readily scalable and the catalyst can be recycled and reused. This catalytic protocol has been applied to the efficient synthesis of a highly potent c-Met kinase inhibitor. Mechanistic studies revealed that uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 63 publications
0
32
0
1
Order By: Relevance
“…Alternatively, organic chlorinating agents, such as N -chlorosuccinimide or iodobenzene dichloride, are used. 18 20 These not only require hypochlorites or chlorine gas for their synthesis 21 , 22 but also generate stoichiometric amounts of organic waste upon usage. Hence, there has been a recent push to develop environmentally benign methods for electrophilic chlorinations.…”
Section: Relevance Of Electrophilic Chlorinationsmentioning
confidence: 99%
“…Alternatively, organic chlorinating agents, such as N -chlorosuccinimide or iodobenzene dichloride, are used. 18 20 These not only require hypochlorites or chlorine gas for their synthesis 21 , 22 but also generate stoichiometric amounts of organic waste upon usage. Hence, there has been a recent push to develop environmentally benign methods for electrophilic chlorinations.…”
Section: Relevance Of Electrophilic Chlorinationsmentioning
confidence: 99%
“…Therefore, in many cases a catalyst must first initially overcome the innate selectivity of the reaction plus an additional ~1.3 kcal/mol to achieve a 9:1 ratio of constitutional isomers (figure 3). 24 Currently there are only few examples in the literature of catalyst controlled regioselective additions in the context of S E Ar, 25,26 including seminal work by Miller selectively brominating complex natural products using a peptide-based catalyst. 27 A regiodivergent approach was pioneered by Lewis using enzymes evolved from RebH to chlorinate indoles and other arenes with stunning site-selectivities.…”
Section: The Regioselective Chlorination Of Phenolsmentioning
confidence: 99%
“…Chlorinated acetanilide is generally afforded by N-chlorosuccinimide (NCS), [14] CuCl 2 , [15] t-BuOCl [16] and a secondary ammonium salt organocatalyst. [17] Koenig et al [18] reported an efficient and practical system for C-H chlorination utilizing a photocatalytic oxidative process based on the organic dye riboflavin tetraacetate that mimicks the enzymatic process. Moreover, Bedford and co-workers [19] reported a solvent-free aromatic C-H chlorination reaction.…”
Section: Expertise In Manufacturingmentioning
confidence: 99%